Selected Items of Information and Their Disclosure in Annual Reports. - Buzby, Stephen L. (The Accounting Review, 1974)
This article presents a study on selected items of information and their disclosure in annual reports in accounting in the U.S. This study has presented the results of a mailed questionnaire survey of financial analysts which sought to determine the relative importance of 38 selected items of information. The extent of disclosure of the 38 items was then measured for a sample of annual reports from 88 small and medium size companies. The results indicated that many of the items were inadequately disclosed in the sample and that the correlation between the relative importance of the items and the extent of their disclosure was small. On the basis of these results, the writer has concluded that an opportunity exists for an expansion of the extent of disclosure in the annual reports of small and medium size companies.